Cross-Sectoral Collaboration in Stunting Prevention: Implementation in Donggala Regency, Central Sulawesi - Fajrillah Kolomboy; Adhyanti Adhyanti; Nurmiaty; Gusman Arsyad; Aminuddin Aminuddin; T. Iskandar Faisal; Kadar Ramadhan; Chen Hana W. Jun (Journal of Public Health and Pharmacy, 2025)
Introduction: The prevalence of stunting in Donggala Regency has increased from 29.5% in 2021 to 32.4% in 2022. The coordination system is not yet optimal, interventions are carried out separately and do not reach the target, and there is no monitoring and evaluation in stunting handling. The objective of the research is to analyze the implementation of cross-sectoral collaboration in stunting handling in Donggala Regency. Methods: This research employs a qualitative methodology, gathering data through in-depth interviews. The 12 informants are members of the Donggala Regency Stunting Reduction Acceleration Team, comprising: The Regional Secretary, The Head of BAPPEDA (Regional Development Planning Agency), The Head of Village Community Empowerment Agency, The Head of Population Control and Family Planning Agency, The Head of Public Works and Housing Agency, The Head of Housi ng and Land Agency, The Head of Health Agency, The Head of Social Agency, The Head of Education and Culture Agency, The Head of Agriculture Agency, The Head of Food Security Agency, The Head of Women's Empowerment and Child Protection Agency, and Puskesmas (Community Health Center). Results: The research findings reveal that while policies and implementation have been initiated, they remain suboptimal due to several factors Independent OPD interventions, Misaligned program targeting, Absence of monitoring and evaluation, Unclear task delineation, Inadequate interpretation of job descriptions. Conclusion: In order to improve stunting interventions, the results highlight the necessity of improved monitoring, explicit role delineation, and increased cross-sectoral collaboration. For stunting prevention initiatives to be effective and long-lasting, policy integration, resource allocation, and community engagement must be strengthened